UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI METODE PEMBELAJARAN KOOPERATIF TIPE STAD PADA MATA PELAJARAN MATEMATIKA DI KELAS VA SDN 007 BAGAN BESAR - Murrah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this research is the poor learning outcomes in mathematics. This is confirmed by observations from 20 students, of whom only 4 completed their study results. This study is a classroom action research aimed at improving learning outcomes through the implementation of the STAD cooperative learning method. The study was conducted at SDN 007 Bagan Besar, with the subjects being students of class V A. The instruments used for data collection included oral tests and written tests conducted after the learning process. The results showed that the application of the STAD cooperative method can improve learning outcomes in mathematics. This is evident from the findings: (1) in the first cycle, mastery of learning outcomes increased by 40%; and (2) in the second cycle, mastery of learning outcomes increased by 75%. Based on these results and the discussion above, it can be concluded that the implementation of the STAD cooperative learning method effectively improves mathematics learning outcomes for class V students at SDN 007 Bagan Besar.